Improving students' critical thinking ability through the inquiry learning model and discovery learning - Putra, Rizka Andhika; Cimari, Tati (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The issue underlying this research is the low critical thinking skills of students in SMAN 3 Ciamis which is caused by the learning process which still uses traditional, one-way methods and does not develop students' thinking skills. The purpose of this study was to determine students' critical thinking skills after applying Inquiry Leaning, Discovery Learning and Conventional methods. The method used is quasi-experimental with a Counterbalance research design. The instrument in the research was multiple choice complex questions that measured students' critical thinking skills. The results of analysis and testing using One Way Anova show that there are differences in students' critical thinking abilities from each treatment carried out in each class with different methods so that the hypothesis proposed can be accepted. Judging from the results of the acquisition of the average value (mean) of students' critical thinking skills in each study, it shows that classes using the Inquiry Leaning model are always higher than the Discovery Learning and conventional models. The conclusion of this study is that the Inquiry Learning model is more effective in improving critical thinking skills compared to Discovery Learning and conventional learning models.